Morbidity Profile of Employees Working in A Thermal Power Station Parali - Kawalkar, U G; Kakrani, V A; Nagaonkar, A S; Vedpathak, V L; Dahire, P L; Kogade, P G (National Journal of Community Medicine, 2014)
Introduction: Health is multi factorial. An individual’s biological makeup influences health through interaction with social and physical environments as well as behavior. In Thermal power station different groups of employees are exposed to different working conditions and environmental factors at their work place; so an attempt has been made to conduct a study on the morbid conditions in employees of Thermal power station. Material and Method: Cross- sectional descriptive study was done. Total 400 employees were studied. History taking included personal and socio-demographic details occupational history, presenting complaints, past history, family history and history of accidents. Interview was followed by thorough clinical examination. Result: Majority of employees worked in Coal Handling Plant 90(22.5%). Respiratory system morbidities were maximum i.e. chronic bronchitis in 53 (13.25%) study subjects. Digestive system morbidities were observed in the form of acid peptic disease in 39 (9.75%) employees. Morbidities of circulatory system were hypertension was diagnosed in 55 (13.75%) study subjects. Under musculoskeletal system, common morbidities present were back pain i.e. in 22 (5.50%), followed by arthritis in 19 (4.75%). Respiratory morbidity viz. chronic bronchitis and bronchial asthma was most common morbidity. Conclusion: For employee working in a power plant, it is highly advised that they must have regular health checkups.